Financial management and accounting in the public sector - Bandy, Gary. 4 0 16; 5 (London : Routledge, Taylor & Francis Group, 2015)
The impact of the global financial crisis on government funds has been significant, with squeezed budgets having to satisfy ever-increasing demands for public services. Managers working in the public sector are confronted daily with targets and demands that are often set in confusing accounting and financial language. In Financial Management and Accounting in the Public Sector, Gary Bandy employs a clear and concise narrative to introduce the core concepts of accounting and financial management in the public sector and how to deliver services that represent value for money.This second edition has been revised and updated throughout, offering:an increased focus on post-crisis austerity more international examples of public financial management greater coverage of governance, accountability and risk management With a glossary of terms to help managers understand and be understood by accountants, as well as learning objectives, case studies and discussion questions, this practical textbook will help students of public management and administration to understand the financial and accounting aspects of managing public services--;The impact of the global financial crisis on government funds has been significant, with squeezed budgets having to satisfy ever-increasing demands for public services. Managers working in the public sector are confronted daily with targets and demands that are often set in confusing accounting and financial language. In Financial Management and Accounting in the Public Sector, Gary Bandy employs a clear and concise narrative to introduce the core concepts of accounting and financial management in the public sector and how to deliver services that represent value for money. This second edition has been revised and updated throughout, offering: - an increased focus on post-crisis austerity - more international examples of public financial management - greater coverage of governance, accountability and risk management With a glossary of terms to help managers understand and be understood by accountants, as well as learning objectives, case studies and discussion questions, this practical textbook will help students of public management and administration to understand the financial and accounting aspects of managing public services--
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Accounting. -- Finance, Public.;Public administration.;Finance, Public -- 20; 20; 2